Household food security in Maputo: the role of Gendered Access to education and employment. Issue 5 (3rd September 2021) - McCordic, C.; Riley, L.; Raimundo, I.
ABSTRACT: Gender-based structural inequalities in Southern African cities continue to drive poverty and food insecurity in spite of decades of development efforts to raise the social, economic, and political status of women relative to men. A 2014 survey of household food security in Maputo found that female headship is closely associated with food insecurity. This article assesses the role of employment and education in explaining this phenomenon in the city of Maputo. Using household survey data, this investigation defines the extent to which the relationship between the sex of the household head and food insecurity appears to be conditionally dependent upon employment and education. The findings provide further impetus to urban policy makers to operationalise gender equality goals.